Angin Santa Ana dan Kebakaran LA: Fenomena Alam atau Teguran Ilahi? - Asfida Rahma; Umi Akromah (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Wildfires in Los Angeles are a phenomenon that can be analyzed from two main perspectives: science and religion. From a scientific standpoint, these fires are triggered by a combination of natural factors, such as the Santa Ana winds that bring hot and dry air, and climate change, which extends drought periods and increases temperatures. However, human activities, including environmental exploitation, deforestation, and inadequate fire mitigation efforts, have exacerbated the situation. From an Islamic perspective, natural disasters can be seen as tests, warnings, or consequences of human negligence in maintaining environmental balance, as mentioned in the Qur'an (Surah Ar-Rum: 41). This study highlights that wildfires are not merely natural occurrences but also have spiritual dimensions. Islam emphasizes that humans are entrusted as stewards of the earth, responsible for preserving nature rather than passively accepting disasters. Therefore, the best approach to addressing wildfires is to integrate scientific understanding with religious values. Proposed solutions include science-based prevention efforts, such as sustainable forest management and fire mitigation policies, as well as spiritual awareness to appreciate and safeguard nature as a divine trust. By understanding the relationship between science and religion, humanity can take greater responsibility in disaster response and establish a more balanced and sustainable way of life.